Discussion: Utilizing waste-shredded rubber pieces for improved foundation stability [Transp. Infrastruct. Geotech. 11(6), 3941-3968] - O'Kelly, Brendan (My University, 2025)
This communication article presents a discussion of various identified shortcomings in the original research paper by Thapa et al. (the Authors) that was recently published in Transp. Infrastruct. Geotech. 11(6), 3941–3968, 2024. The Authors investigated the application of waste shredded rubber pieces (SRPs) for improving the performance of shallow foundations bearing on a problematic collapsible soil obtained from the Western Uttar Pradesh region of India. They performed laboratory experiments, including Atterberg (consistency) limits, compaction, unconfined compressive strength and undrained direct-shear tests, on the unamended soil (i.e., 0% SRP content) and five soil–SRP blends prepared with gravimetric SRP contents ranging from 1% to 5%. Moreover, the Authors employed finite-element method (FEM) modeling to assess the effects of SRP content on the ultimate bearing capacity (B) and settlement (S) response of an infinite strip footing bearing on the investigated compacted soil–SRP blends. Using the results obtained from the six FEM simulations, the Authors then produced multiple linear regression (MLR) models for predicting the FEM-generated B and S values of the compacted soil amended with 0–5% SRP additive. In this communication article, the Discussers raise several shortcomings of the Authors’ research, including (i) the presented Atterberg limits results are fundamentally compromised by the inclusion of the coarse SRP additive in the test material, and (ii) the validity and applicability of their proposed MLR models for predicting the B and S responses of shallow footings bearing on the SRP amended soil.
PUBLISHED
Keywords: Shredded rubber pieces, Atterberg limits, Shallow foundation, Multiple regression; Smart & Sustainable Planet; CLIMATE CHANGE; Soil improvement; Environmental engineering; GEOTECHNICAL ENGINEERING; Geoenvironmental engineering; Geotechnics; Natural Hazards; Soil Mechanics; Soil Sciences, Conservation; Soil Sciences, Erosion; Soil processes; climate change impacts; geoenvironment; geotechnical; wildfire; wildfires